2020
DOI: 10.1155/2020/6415083
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Effect of Electroacupuncture Therapy for Ischemic Stroke

Abstract: Electroacupuncture (EA) stimulation is a supplementary therapy and commonly applied in treatment of ischemic stroke in clinic. Stroke is an important cause of long-term disability in individuals in both developing and developed countries. In our review, we show the application of EA stimulation for apoplectic pain, limbs spasticity, blood flow interruption, depression, swallowing dysfunction, aphasia, urinary incontinence, cognition and memory impairment, and constipation following stroke in patients and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 62 publications
0
19
0
1
Order By: Relevance
“…The mechanisms of action have been investigated in several studies, which have shown a reduction in reperfusion inflammatory reactions and ferroptosis [ 34 , 35 ]. EA has the advantages of continuous acupuncture, relatively fixed parameters, and reduced manpower and has been suggested as a strategy to combat damage caused by cerebral ischemia [ 21 ]. Baihui (GV20) is often selected as a treatment for cerebral ischemia because it has many functions in traditional Chinese medicine, such as dredge collateral, regulation of qi flow, restoration of consciousness, and benefitting resuscitation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of action have been investigated in several studies, which have shown a reduction in reperfusion inflammatory reactions and ferroptosis [ 34 , 35 ]. EA has the advantages of continuous acupuncture, relatively fixed parameters, and reduced manpower and has been suggested as a strategy to combat damage caused by cerebral ischemia [ 21 ]. Baihui (GV20) is often selected as a treatment for cerebral ischemia because it has many functions in traditional Chinese medicine, such as dredge collateral, regulation of qi flow, restoration of consciousness, and benefitting resuscitation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…EA has been used as an effective and safe treatment for various diseases, especially brain diseases and their rehabilitation [ 20 ]. The effectiveness of electroacupuncture involves the acupuncture points, interval, intensity, and duration of intervention for stroke treatment [ 21 ]. Compared with other acupoints, we chose Baihui (GV20) and Zusanli (ST36).…”
Section: Introductionmentioning
confidence: 99%
“…When the acupuncture point has a sense of qi, the therapist selects the wave type, slowly adjusts to the required output current, and performs electrical stimulation generally for 5–20 min. Numerous studies have demonstrated the cognitive improvement effects of EA stimulation over the past several years ( 11 , 12 ). EA applied before surgery can effectively reduce the dose of narcotic drugs, improve stress response, reduce the occurrence of postsurgical complications, and promote functional rehabilitation in patients undergoing surgery ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Electroacupuncture (EA) combines traditional acupuncture and modern electrical stimulation and has been widely used in the clinical setting. It can considerably improve the neurological function and quality of life of patients ( 9 , 10 ). EA not only offers strong and stable stimulation but also can be applied to multiple targets ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%